Utility of mHealth initiatives in the Indian context - Gunamany, Susanna (International Journal Of Community Medicine And Public Health, 2022)
India is the second-largest nation in the world, with two-thirds of its population living in rural areas. The demographic and environmental shift of the country is augmenting the already existing high burden of public health concerns. India has improved the prevailing health scenario despite several limitations like vast geographical area, lack of quality transportation facilities, high population density, undernutrition, illiteracy, and poverty in the past decade. These factors continued to be the underlying causes to slow down the pace of achieving an efficient healthcare system. Significant disease burden of communicable and non-communicable diseases, poor health infrastructure, limited human resources at government facilities, accessibility issues related to health care by rural inhabitants increases the existing catastrophes in health care delivery in the country. This paper aims to analyse the utility of mHealth initiatives in the Indian context. For a developing nation like India, mHealth provides access to people, including rural populations located in remote locations with limited access to healthcare facilities. mHealth solutions could cater to different kinds of health needs, depending on the demographic characteristics and type and access to a mobile phone a user may have. It is more beneficial for a country like India. It becomes nearly impossible for the urban population to regularly visit a healthcare facility due to the limited infrastructure and human resources, the condition of healthcare facilities and the pressure on care providers. The use of mobiles for reaching out to many consumers across the country, especially the vast rural population, for information dissemination, education, consultation and monitoring will be the actual use of mHealth.